2018
DOI: 10.3758/s13423-018-1454-5
|View full text |Cite
|
Sign up to set email alerts
|

Serial dependence in position occurs at the time of perception

Abstract: Observers perceive objects in the world as stable over space and time, even though the visual experience of those objects is often discontinuous and distorted due to masking, occlusion, camouflage, or noise. How are we able to easily and quickly achieve stable perception in spite of this constantly changing visual input? It was previously shown that observers experience serial dependence in the perception of features and objects, an effect that extends up to 15 seconds back in time. Here, we asked whether the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
167
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(193 citation statements)
references
References 56 publications
(83 reference statements)
23
167
2
1
Order By: Relevance
“…We previously observed a similarly strong serial dependence on items that are retro-cued but not reported (omission of the response phase in a subset of trials) as on reported targets 15 (see also refs. 3,7 ). This makes it unlikely that the report itself is responsible for the enhanced serial dependence on targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed a similarly strong serial dependence on items that are retro-cued but not reported (omission of the response phase in a subset of trials) as on reported targets 15 (see also refs. 3,7 ). This makes it unlikely that the report itself is responsible for the enhanced serial dependence on targets.…”
Section: Discussionmentioning
confidence: 99%
“…This bias was enhanced by spatial and temporal item proximity as well as by attentional selection and was termed 'serial dependence'. It has since been observed for other modalities, including facial identity and expression 4,5 , spatial positions 6,7 , numerosity [8][9][10] or ensemble representations 11 . As serial dependence reduces differences in the appearance of similar consecutive objects, it has been interpreted as promoting perceptual stability and continuity of a visual object over time 3 .…”
mentioning
confidence: 93%
“…In contrast to repulsive adaptation, recent studies have found that perceptual decisions about stimulus features can be attracted towards stimuli encountered in the recent past -a phenomenon termed attractive serial dependence . Like repulsive adaptation, attractive serial dependence has now been reported for a large variety of visual features, such as orientation (Cicchini et al, 2017;Czoschke et al, 2019;Fritsche et al, 2017), numerosity (Cicchini et al, 2014;Corbett et al, 2011;Fornaciai and Park, 2018) and spatial location (Bliss et al, 2017;Manassi et al, 2018;Papadimitriou et al, 2016). This phenomenon may represent a (Bayes-)optimal strategy of decoding the sensory information into a perceptual decision (Cicchini et al, 2018;van Bergen and Jehee, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…In line with this idea, recent studies have found that perceptual decisions about a large variety of visual stimulus features are biased towards features encountered in the recent past. Such features include orientation (Cicchini & Burr, 2017;Czoschke, Fischer, Beitner, Kaiser, & Bledowski, 2018;Fritsche et al, 2017), numerosity (Cicchini, Anobile, & Burr, 2014;Corbett, Fischer, & Whitney, 2011;Fornaciai & Park, 2018a), spatial location (Bliss, Sun, & D'Esposito, 2017;Manassi, Liberman, Kosovicheva, Zhang, & Whitney, 2018;Papadimitriou, White, & Snyder, 2016), visual variance (Suárez-Pinilla, Seth, & Roseboom, 2018), face identity (Liberman, Fischer, & Whitney, 2014), emotional expression and attractiveness (Xia, Leib, & Whitney, 2016). While it is still debated whether such serial dependence biases are introduced at a perceptual stage or at a post-perceptual, decision or short-term memory stage (Fritsche et al, 2017;Bliss et al, 2017;Cicchini & Burr, 2017;Fornaciai & Park, 2018a), the ubiquity of serial dependencies in perceptual decisions is striking and suggests that serial dependencies might arise from a general computation of the brain, potentially reflecting the stabilization of neural representations.…”
Section: Introductionmentioning
confidence: 99%